EXPLORING THE IMPACT FACTORS TO VALUE CO-CREATION OF RESIDENTS IN DA LAT CITY - Phạm, Viết Cường (Trường Đại học Đà Lạt, 2023)
This study evaluated the factors affecting residents’ value co-creation based on their attitudes towards tourism development, community attachment, and interactions with tourists. The study was conducted using structural equation modeling to analyze data from 481 residents of Da Lat city, Lam Dong, Vietnam. The research results reveal that residents’ value co-creation is impacted by community attachment, interactions with tourists, and attitudes toward tourism development. The most impactful factor on residents’ value co-creation is their attitudes toward tourism development. However, the relationship between the residents’ interactions with tourists and their attitudes toward tourism development gives no significant results. Finally, the study proposes some managerial implications for the authorities and service providers.